The CFA Arrangements : More than Just An Aid Substitute? - Yehoue, Etienne (IMF Working Papers; Working Paper ;, 2007)
The CFA franc zone has had one of the longest experiences with a fixed exchange rate for a convertible currency and regional integration of any group of developing countries. France, the anchor country, provides aid to support the zone. This paper asks whether the arrangements are more than just an aid substitute. The paper addresses this issue by evaluating the overall performance of the zone over the period 1960-2004. The analysis reveals that when the zone is hit by a negative shock, France increases its aid, thereby acting as a shock absorber. However, it also finds that the zone displays strong performance in two areas-price stability and fiscal policy. Thus the paper concludes that the arrangements are not an aid substitute; they have real macroeconomic value for the zone and complement aid.